THE EFFECT OF SERVICE QUALITY AND PRICE ON CUSTOMER RETENTION MEDIATED BY CUSTOMER SATISFACTION IN THE OUTPATIENT UNIT OF RHC LAMPUNG CLINIC - Yani Puji Mustika Sari; Hery Winoto Tj; Fushen (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study is motivated by the increasing competition in the healthcare sector, especially clinics, which requires effective strategies in retaining patients. Stagnation and decline in the number of patients in 2023 are challenges for RHC Clinic in maintaining the level of visits, which are influenced by service quality and price. Customer retention is a crucial factor for the sustainability of the clinic, considering that the cost of attracting new customers is higher than retaining existing ones. Therefore, this study aims to analyze the effect of service quality and price on customer retention with customer satisfaction as the mediation. With a quantitative approach and purposive sampling method, this study involved 90 outpatient respondents at RHC Clinic, and data analysis was carried out using linear regression and Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with WarpPLS 8.0 software. The results showed that service quality and price had a positive effect on customer satisfaction, which in turn had a positive effect on customer retention, with customer satisfaction as a significant mediating variable. These findings confirm that improving service quality and adjusting prices according to patient expectations play an important role in increasing patient satisfaction and retention. Therefore, the results of this study are expected to be a reference for RHC Clinic management in designing more optimal health service strategies to increase customer retention.